Autogenous bone graft for management of periodontal defects - Sneha Kataria; Kabbur Thippanna Chandrashekar; Rohit Mishra; Vandana Tripathi (Wolters Kluwer Medknow Publications, 2016)
The aim of this article is to present the use of autogenous bone graft for regenerative management of infrabony and furcation osseous defects. A trephine bur (Auto Chip Maker ® ) was used to obtain autograft from the anterior mandibular region. It is considered as the "gold standard" bone graft, but the difficulty in harvesting it and the increased chairside time have reduced its popularity. This report highlights the use of Auto Chip Maker ® to harvest autograft for management of periodontal osseous defects.